Peran Transformational Leadership untuk Meningkatkan Innovative Work Behavior Menuju Bantul Smart City - Sasmita Wijayanti, Nadia; Yoga Bumi Pradana, I Putu (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This research aims to analyze the role of regional leaders in the Bantul District Government in promoting innovative work behavior of civil servants in the Lapor Bantul program in order to optimize Bantul Smart City. This study departs from the phenomenon of efforts to improve services carried out by the Bantul District Government to foster innovative behaviors. In uncovering these phenomena, this research will analyze to what extent and how the role and actions taken by regional leaders in the Bantul District related to the Lapor Bantul program in mobilizing employees and other stakeholders so that they can contribute to and participate in the development of Bantul District together. Lapor Bantul was chosen as the focus of the research because it is a priority program indicator for the realization of Bantul Smart City. There still needs to be efforts for resident engagement and better integration among various stakeholders so that the dimension of smart society can be realized optimally. Based on purposive sampling technique, 3 informants were determined for the research, namely the Secretary of the Bantul District, the Head of the Lapor Bantul Department, and the Head of DISKOMINFO, considering their experience in policy making and program implementation for a minimum of 3 years. Data collection techniques used observation, documentation, and in-depth interviews with qualitative data analysis methods including data reduction, data display, and the conclusion.